First Results of National Surgical Site Infection Surveillance in Hungary - Böröcz, K; Szilagyi, E; Kurcz, A (International Journal of Infection Control, 2009)
Healthcare-associated infections (HAI) are an important cause of morbidity and mortality, prolongs hospital stay, increases antibiotic usage, add costs.1 The surveillance of HAI has been acknowledged as an important component of infection control programmes, and is increasingly recognised as key to improving clinical outcomes.2Hungarian National Nosocomial Surveillance System (HNNSS) was established in 2004. The aim of this system has been to create a national database of HAI, to enable hospitals to perform surveillance of HAI and compare their results with national aggregated data and use the information to improve patient care.3 HNNSS is a standardized, secure web-based reporting system. It has 2 components: a mandatory and a voluntary part. Software is offered free for hospitals. Mandatory components are reports of nosocomial outbreaks, infections caused by multidrug resistant organisms and nosocomial bloodstream infections. Participation of hospitals in surveilance component is voluntary and confidential. Surveillance compontents are: intensive care unit (ICU) and surgical site infections (SSI). All data are received and analysed by National Center for Epidemiology. Reports of surveillance data are elaborated every six months. SSI surveillance started in November 2004. Hospitals can choose one or more of 36 defined categories (CDC-NNIS). With SSI surveillance component we joined European Surveillance network HELICS (Hospitals in Europe Link for Infection Controlthrough Surveillance).